VIOLENT CRIME IN BRISTOL: An Accident and Emergency Department Perspective - Shepherd, Jonathan (The British journal of criminology, 1990)
A victim survey was conducted in a large city centre hospital accident and emergency department serving a well-defined population. Those most at risk of violence were similar to risk groups identified in previous crime surveys. Compared to the hospital catchment population, males aged 16-29 years, those resident in the most socially and materially deprived electoral areas, single people, skilled manual workers, and the unemployed were significantly over-represented. Males attended for treatment most often at the weekend between 11.00 p.m. and 3.00 a.m. while females attended more evenly through the week. The incidence of domestic violence was higher than that reported in the British Crime Surveys. Overall, numbers of victims increased with increasing hours of daylight during the first five months of the year. Most assaults took place in the street or in public houses or discotheques, though female victims were most often assaulted in their own home, usually after an argument. Accident and Emergency Department data are a useful source of information about violent crime